A STUDY OF IDIOMATIC EXPRESSIONS IN THE TV MINISERIES “WANDA VISION” DIRECTED BY MATT SHAKMAN - Sarsono, Sarsono; Zayyan, Arianto Abid; Abdulloh, Abdulloh; Suprihandani, Eny (STIBA IEC JAKARTA, 2023)
The Objectives of the research are to find out the idiomatic expressions, to identify kinds of the idiomatic expressions, and find out the meaning of the idiomatic expressions found in the Wanda Vision TV miniseries. Some phrases in English language cannot be understood literally. A reader often needs to see the whole unit to understand the context of the phrases and these phrases are called idiom. The writer uses qualitative method to gain the objectives of the study. The researcher already collected the data from the script of the miniseries and categorized the idiomatic expression. The total number of idiom expressions is105. The categories found are 4 similes, 2 binomials, 5 proverbs, 9 clichés, and 85 fixed statements. And each idiomatic expressions meaning could be defined. The conclusion from the data gathered based on the 105 idiomatic expressions found in the Wanda Vision TV miniseries is fixed statement idiomatic expressions frequently used